ANALYSIS AND ECONOMIC EVALUATION OF DEPOSIT REFUND SYSTEM - Atstāja, Dzintra; Lukševica, Līva; Cudečka-Puriņa, Natālija; Vesere, Rudīte; Susniene, Rozita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The aim of this research is to analyse the deposit refund system and to perform economic evaluation of deposit refund system implementation in Latvia. To achieve this, the authors will use following methods: gathering and further analysis of statistical data, comparative analysis and cost benefit analysis. Main conclusions of the research reveal that despite being a costly solution, deposit refund system brings certain benefits and the payback period can be approximately ten years. Moreover, with the increase of the deposit fee the overall financial ratios of the system can be significantly improved.